Efficacy of dextromethorphan for the treatment of depression: a systematic review of preclinical and clinical trials. (2nd January 2021) - Majeed, Amna; Xiong, Jiaqi; Teopiz, Kayla M.; Ng, Jason; Ho, Roger; Rosenblat, Joshua D.; Phan, Lee; Cao, Bing; McIntyre, Roger S.
ABSTRACT: Introduction: The large percentage of adults with major depressive disorder (MDD) insufficiently responding and/or tolerating conventional monoamine-based antidepressants invites the need for mechanistically novel treatments. Convergent evidence implicates glutamatergic signaling as a potential therapeutic target in MDD. Areas covered: The synthesis herein of preclinical and clinical studies indicates that dextromethorphan (DXM) is well tolerated and exhibits clinically significant antidepressant effects; DXM combined with bupropion has demonstrated replicated and relatively rapid onset efficacy in adults with MDD. DXM efficacy has been preliminarily reported in adults with bipolar depression. The combination of DXM and bupropion represents a pharmacokinetic and pharmacodynamic synergy which may account for the rapidity of action in MDD. Expert opinion: The combination of DXM and bupropion is a safe, well tolerated and efficacious treatment option in adults with MDD. Priority questions are whether DXM/bupropion is uniquely effective across discrete domains of psychopathology (e.g. anhedonia, reward processing, general cognitive systems) and/or whether it is able to significantly improve patient-reported outcomes (e.g. quality of life, psychosocial functioning). The availability of ketamine/esketamine and DXM/bupropion instantiates the relevance of glutamate as a treatment target in MDD. Studies in bipolar depression with DXM/bupropion are warranted as well as in MDD with suicidality.